VARIABILITY IN GRAIN QUALITY PARAMETERS OF WHEAT GENO-TYPES GROWN IN DIFFERENT LOCATIONS: QUALITY PARAMETERS OF WHEAT GENOTYPES GROWN IN DIFFERENT LOCATIONS - Nikolić, Valentina (Journal on Processing and Energy in Agriculture, 2026)
Wheat is a staple food for many nations worldwide, providing essential nutrients and energy. Five local wheat cultivars were grown at four different locations in Serbia to investigate variations in grain quality. Standard laboratory procedures were used to analyze grain test weight, chemical composition, and gluten content of whole-wheat flour. The test weight of all samples ranged from 71.20 to 80.76 kg/hl, making them suitable for industrial purposes (≥73 kg/hl). However, only 65% of the samples met the quality requirement for human consumption (≥76 kg/hl), as specified by Serbian regulations on the quality of grain, mill, bakery products, and pasta. Gluten content varied from 20.9% to 43.8%. The highest starch content was found in the cultivar Aurelija from Donja Trepča (67.46% d.m.), while the highest protein content (16.04% d.m.) was observed in the cultivar Osatka from Zemun Polje. Significant differences in chemical composition, gluten content, and test weight were noted among the genotypes and across locations. The findings indicate that both genotype and location (i.e., environment) have a considerable effect on grain quality. Nevertheless, these quality parameters are considered high quality under Serbian regulations for cereal grains and products.